2013
DOI: 10.3389/fpsyg.2013.00468
|View full text |Cite
|
Sign up to set email alerts
|

Predicting musically induced emotions from physiological inputs: linear and neural network models

Abstract: Listening to music often leads to physiological responses. Do these physiological responses contain sufficient information to infer emotion induced in the listener? The current study explores this question by attempting to predict judgments of “felt” emotion from physiological responses alone using linear and neural network models. We measured five channels of peripheral physiology from 20 participants—heart rate (HR), respiration, galvanic skin response, and activity in corrugator supercilii and zygomaticus m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…5 ). This was in line with prior researches 5 6 13 14 31 34 . In the present study, a HMPM can give a better description of nonlinearities of the SCR affective process than what a linear model can do.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…5 ). This was in line with prior researches 5 6 13 14 31 34 . In the present study, a HMPM can give a better description of nonlinearities of the SCR affective process than what a linear model can do.…”
Section: Discussionsupporting
confidence: 92%
“…Further more, continuously estimating individual affect can supply more quantitative results than what classification procedures can supply. Methods of estimating human affective states, such as multivariate linear-regression analysis (MLR), partial least-square estimation (PLS), genetic algorithm optimized support vector regression (GA-SVR), artificial neural network (ANN), bidirectional long short-term memory neural networks (LSTM-NNs), fuzzy logical analysis (FLA), and sequence Bayessian analysis (SBA), have been proposed in the past decade 28 29 30 31 32 33 34 . Although their performances differ with each other, these computational models achieve relative good results to some extent, and supply us a good prospect in affective estimation.…”
mentioning
confidence: 99%
“…Previous research has shown that non-linear methods can be particularly useful in situations where linear methods are insufficient to model the relationship between dependent and independent variables. Artificial neural networks may be used as a non-linear regression method (Coutinho and Cangelosi, 2011 ; Russo et al, 2013 ; Vempala and Russo, 2013 ) to predict valence, tension arousal, and energy arousal ratings using timbre descriptors.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, emotional arousal is associated with sympathetic ANS activity [ 1 ], thus leading to an increase in HR, whereas parasympathetic ANS activity leads to a decrease in HR [ 24 ]. Accordingly, several studies reported (trends towards) higher HR with arousing music compared to tranquilizing or less arousing music [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. However, when comparing HR during music listening to baseline measurements, previous studies do not provide a consistent picture: Although some studies demonstrated an increase in HR with arousing music and a decrease in HR with tranquilizing music [ 25 , 27 ], others reported increases in HR with arousing as well as tranquilizing music [ 26 , 34 ], decreases in HR with tranquilizing as well as arousing music [ 29 , 35 ], or differences in HR despite similar music-evoked arousal [ 36 ].…”
Section: Introductionmentioning
confidence: 99%